Supplemental Fibrinogen Restores Platelet Inhibitor-Induced Reduction in Thrombus Formation without Altering Platelet Function: An In Vitro Study - Bärnthaler, Thomas; Mahla, Elisabeth; Toth, Gabor G.; Schuligoi, Rufina; Prüller, Florian; Buschmann, Eva; Heinemann, Akos (Thrombosis and Haemostasis, 2020)
Background For patients treated with dual antiplatelet therapy, standardized drug-specific 3-to-7 day cessation is recommended prior to major surgery to reach sufficient platelet function recovery. Here we investigated the hypothesis that supplemental fibrinogen might mitigate the inhibitory effects of antiplatelet therapy.Methods and Results To this end blood from healthy donors was treated in vitro with platelet inhibitors, and in vitro thrombus formation and platelet activation were assessed. Ticagrelor, acetylsalicylic acid, the combination of both, and tirofiban all markedly attenuated the formation of adherent thrombi, when whole blood was perfused through collagen-coated microchannels at physiological shear rates. Addition of fibrinogen restored in vitro thrombus formation in the presence of antiplatelet drugs and heparin. However, platelet activation, as investigated in assays of P-selectin expression and calcium flux, was not altered by fibrinogen supplementation. Most importantly, fibrinogen was able to restore in vitro thrombogenesis in patients on maintenance dual antiplatelet therapy after percutaneous coronary intervention.Conclusion Thus, our in vitro data support the notion that supplementation of fibrinogen influences the perioperative hemostasis in patients undergoing surgery during antiplatelet therapy by promoting thrombogenesis without significantly interfering with platelet activation.
Keywords: fibrinogen; platelet inhibitors; platelets; ticagrelor; acetylsalicylic acid